Fisetin Modulates Human Oral Squamous Cell Carcinoma Proliferation by Blocking PAK4 Signaling Pathways - Li Y; Jia S; Dai W (Dove Medical Press, 2020)
Yanshu Li, 1–3 Shiheng Jia, 3, 4 Wei Dai 5, 6 1Key Laboratory of Cell Biology, Ministry of Public Health, China Medical University, Shenyang, Liaoning, People’s Republic of China; 2Key Laboratory of Medical Cell Biology, Ministry of Education, China Medical University, Shenyang, Liaoning, People’s Republic of China; 3Department of Cell Biology, China Medical University, Shenyang, Liaoning, People’s Republic of China; 4Department of Clinical Medicine, China Medical University, Shenyang, Liaoning, People’s Republic of China; 5Department of Oromaxillofacial-Head and Neck Surgery, School of Stomatology, China Medical University, Shenyang, Liaoning, People’s Republic of China; 6Department of Oral and Maxillofacial Surgery, School and Hospital of Stomatology, China Medical University, Liaoning Provincial Key Laboratory of Oral Diseases, Shenyang, Liaoning, People’s Republic of ChinaCorrespondence: Wei DaiDepartment of Oral and Maxillofacial Surgery, School and Hospital of Stomatology, China Medical University, Liaoning Provincial Key Laboratory of Oral Diseases, Shenyang, Liaoning 110002, People’s Republic of ChinaTel +86 139 0988 4820Email daicmu@163.comObjective: Human oral squamous cell carcinoma (OSCC) is a major cause of mortality and morbidity worldwide. There is an urgent need to identify bioactive molecules and potential target genes that could inhibit carcinogenesis for OSCC therapy. Fisetin (3,7,3′,4′-tetrahydroxyflavone), a naturally occurring flavonoid, has been previously shown to have anti-proliferative activities in OSCC; however, its molecular mechanism is unknown.Methods: Colony formation, cell viability, Boyden chamber, wound healing, and tumor xenograft assays were used to detect the impact of fisetin on OSCC cells in vitro and in vivo. Western blot analysis was used to examine the corresponding protein expression.Results: Fisetin treatment significantly inhibited proliferation and promoted apoptosis by repressing PAK4 expression. Moreover, fisetin treatment attenuated cell migration by blocking PAK4 signaling pathways. In addition, the tumor xenograft showed anti-tumor growth effects of fisetin exposure in vivo.Conclusion: Fisetin may represent a potential therapeutic strategy for human OSCC by targeting PAK4 signaling pathways.Keywords: OSCC, fisetin, PAK4, PARP